Design, implementation, and evaluation of a diabetes educational game for the pharmacy students: A parallel-group study - Sholeh Ebrahimpour; Eisa Rezaei; Soha Namazi; Mehdi Mohammadi (Tusiah-i amuzish dar ulum-i pizishki-i Zanjan, 2023)
Background & Objective: The objectives of this study were to design, implement, and evaluate an educational game on the diagnosis and management of diabetes for pharmacy students. Materials & Methods: Educational content for diabetes was prepared and used to design a multimedia file and game scenario. The game was validated and consisted of 25 stages of diagnosing and managing diabetes. Participants were 8th-semester pharmacy students who were divided into two groups. Groups A and B had 10-day access to the multimedia and game files, respectively. Pretest and post-test were held to evaluate students’ learning, and the final exam was used to assess retention. Moreover, user experience was evaluated by a modified and validated version of the Model for the Evaluation of Educational Games questionnaire. Results: A total of 154 students participated in the study. The mean ranks were 69.25 and 60.99 (P=0.808) in the pretest; 64.80 and 67.63 (P=0.551) in the post-test; and 67.44 and 62.19 (P=0.490) in the final exam for groups A and B, respectively. Ninety-nine participants completed the quality questionnaire of the study. The students confirmed the quality of the game in nearly all quality dimensions. About 80 percent of the game users preferred it over usual teaching methods. Conclusion: A high-quality educational game for diabetes was designed and implemented. Although the use of the game was not associated with increased learning or retention scores, pharmacy students preferred it over traditional teaching methods.